Performance Analysis of Retail Salesmen at Pt. Surya Madistrindo Area Office Palu - Ardi Ardi; Burhanuddin Burhanuddin; Sarifuddin Sarifuddin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2020)
This research was conducted at the office of PT Surya Madistrindo Area Office Palu; it aims to determine the Retail Salesman's performance of PT Surya Madistrindo Area Office Palu. The researcher took the entire Salesman Retail PT Surya Madistrindo Area Office Palu, totaling 22 respondents for the population and sample. This study uses primary data taken by distributing questionnaires to all 22 respondents using a census. While the analysis used is descriptive qualitative processed using percentages, qualitative data will be described by words or sentences separated according to categories to obtain conclusions. From the results of the analysis that the researchers conducted, it can be seen that the performance of the Retail Salesman of PT Surya Madistrindo Area Office Palu is at a relatively good level, this is in all research variables, namely Knowledge About Work, Quality of Work, Productivity, Adaptation, Initiatives, and Problem Solving, Cooperation, Responsibility and Ability in Communicating and Interacting. Based on the established assessment criteria, it can be concluded that the Performance Analysis of the Retail Salesman of PT Surya Madistrindo Area Office Palu is quite good. Things that can be recommended in this study such as organizational management, which only emphasizes the procedural approach, but must be refined through changes in vision and mission, techniques, strategies, and operational activities to create excellent teamwork, work relationships based on a participatory approach and workgroups (collaboration). ) to achieve the organizational mission that is efficient, effective and towards a better direction.